SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI RUANGAN X-RAY KONVENSIONAL UNIT RADIOLOGI RSIA ZAINAB - Ehlis Sri Ayuni; Tengku Mohammad Yoshandi; Devi Purnamasari (STIKes Payung Negeri Pekanbaru, 2022)
The occupational health and safety management system (SMK3) is part of the company's overall management system in order to control risks related to work activities in order to create a safe, efficient, and productive workplace. The 5 basic principles of implementing SMK3 are: OHS Policy, Planning, Planning Implementation, Monitoring OHS Performance Evaluation and OHS Performance Improvement Review. At RSIA Zainab, the exposure of images in the exposure room uses a shielding door to protect radiation workers with a distance of approximately 1.5 meters from x-rays, in other hospitals that researchers have observed, the process of patient exposure is different from RSIA, the exposure process is carried out by workers outside the room. irradiation/exposure. The purpose of this research is to find out whether the occupational safety and health management system has been running at RSIA Zainab by examining 3 basic principles of implementing Management system OHS namely: OHS Policy, OHS Performance Evaluation Monitoring and OHS Performance Improvement Review. This research uses descriptive qualitative research through field observations, interviews, documentation and literature studies. The study was conducted at the Radiology Unit of RSIA Zainab in April-June 2021. Management system OHS at RSIA Zainab has been running, but from the 3 basic principles of Management system OHS studied there is 1 principle that is no longer running, namely reviewing and improving OHS performance due to lack of implementation, constrained by financial costs and evaluation so that it is integrated into the OHS policy program. In order to achieve the objectives of the Occupational Health and Safety Management System Principle, the hospital must re-organize the OHS Performance Review and Improvement Program because to improve the OHS performance and improvement of the hospital, there must be a review and improvement of OHS performance.